ANALYSIS OF RISK FACTORS AND ASSESSMENT OF THE COURSE OF AVASCULAR NECROSIS OF THE FEMORAL HEAD IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS - Kovalenko, V.M.; Protsenko, H.O.; Dubas, V.V. (World of Medicine and Biology, 2023)
Avascular necrosis of the femoral head is, although relatively rare, one of the most serious complications of systemic lupus erythematosus. The study focuses on searching for clinical and laboratory features of patients suffering from this complication, as well as on studying its consequences. Data from 149 patients with systemic lupus erythematosus were analyzed, 13 of whom were diagnosed with avascular necrosis of the femoral head. These patients were found to have significantly higher total doses of glucocorticoids, levels of cholesterol and uric acid in serum (at the time of diagnosis of the femoral head avascular necrosis); among clinical presentations, alopecia, lymphopenia and vascular pathology are more common. It has been established that the late age of systemic lupus erythematosus onset correlates with the early development of avascular necrosis of the femoral head. When analyzing the course of the disease, it was revealed that in 9 out of 13 patients, there was a need for arthroplasty of one or both hip joints. Thus, the issue of identifying risk factors and prevention of this complication is especially relevant; consequently, the description of even a small group of such patients may in the future help to study this problem comprehensively.